338 Nutrient for Neuroprotection: MRI Assessment of Lactoferrin Supplementation after HI Injury in the P3 Rat Brain. (October 2012) - Looij, Y van de; Chatagner, A; Huppi, P; Gruetter, R; Sizonenko, S
Abstract : Background: Animal models of preterm brain injury can be achieved by Hypoxia-Ischemia (HI). Lactoferrin (Lf) is an iron-binding glycoprotein with anti-oxidant, anti-inflammatory and anti-infectious activities. In rodents, after oral administration, Lf is rapidly transferred from the intestine into the brain. Aim: The aim of this work was to assess the neuroprotective effect of Lf supplementation trough lactation after P3 HI brain injury by using MRI. Methods: At birth, rat pups were divided in 3 groups: The dams of the HI-Lf group (n=6) received Lf-enriched food, HI-Iso received a diet isocaloric to the Lf (n=6) and a Sham group (n=3). At P3 pups from HI-Lf and HI-Iso groups underwent HI injury. At P25, T2 W images, 1H-MRS and DTI were performed. A Mann-Whitney test was used to compare values between the different groups. Results: When compared to HI-Iso group, the number of rats injured (51% vs. 61%), the percentage of injured cortex at P3 (4.9±3.6% vs. 15.0±7.1%, P =0.02) as well as the percentage of cortical loss at P25 (4.6±4.8% vs. 16.7±11.9%, P =0.09) were reduced in the HI-Lf group. At P25, using 1H-MRS, brain metabolites of HI-Lf rats is almost normalized with [Glu+Gln] only remaining decreased whereas the Iso-HI group showed also decreased levels of [Asp] and [totalNAA]. With DTI, white matter FA values tend to be higher in the HI-Lf group than in the HI-Iso group and were comparable to Sham. Conclusion: This study shows a potential neuroprotection from maternal nutritional supplementation with Lf after HI in the developing brain of progeny.